Bulk properties of the system formed in Au plus Au collisions at √sNN=14.5 GeV at the BNL STAR detector - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert; Weidenkaff, Philipp (Physical review, 2020)
We report systematic measurements of bulk properties of the system created in Au + Au collisions at root S-NN = 14.5 GeV recorded by the STAR detector at the Relativistic Heavy Ion Collider (RHIC). The transverse momentum spectra of pi(+/-), K-+/-, and p((p) over bar) are studied at midrapidity (vertical bar y vertical bar < 0.1) for nine centrality intervals. The centrality, transverse momentum (p(T)), and pseudorapidity (eta) dependence of inclusive charged particle elliptic flow (v(2)), and rapidity-odd charged particles directed flow (v(1)) results near midrapidity are also presented. These measurements are compared with the published results from Au + Au collisions at other energies, and from Pb Pb collisions at root S-NN = 2.76 TeV. The results at root S-NN = 14.5 GeV show similar behavior as established at other energies and fit well in the energy dependence trend. These results are important as the 14.5-GeV energy fills the gap in mu(B), which is of the order of 100 MeV, between root S-NN = 11.5 and 19.6 GeV. Comparisons of the data with UrQMD and AMPT models show poor agreement in general.
Gesehen am 07.04.2020
SNN steht unter dem Wurzelzeichen